Factors Affecting Overseas Internship, Employment and Further Education under the Background of "Belt and Road Initiative" - A TPB Model Analysis - Jun Hao, Chen; Norizan, Jaafar; Sin, Kit Yeng (UNIMAS Publisher, 2022)
The Belt and Road Initiative is a long-term foreign development strategy that China adheres to. However, the key to the promotion of the Belt and Road is the investment of a large number of high-quality international talents. In order to promote international talents to go abroad, it is not only necessary to deepen the system level and multilateral cooperation at the diplomatic level, but also to cultivate human resources with the willingness and ability to move internationally to make full use of their capabilities. From the perspective of the TPB model, this paper adopts the method of structural equation model, and takes an application-oriented university in Henan Province, China as the research object, to explore the influencing factors of overseas internship, employment and further study for college students. The results show that attitudes, subjective norms and perceived behavioural control all have significant effects on behavioural intention. Usefulness had no significant effect on behavioural intention; Usefulness has a significant effect on behavioural intention through attitude. Therefore, according to the conclusion, relevant suggestions are put forward for schools, teachers and students respectively.